PENGARUH HARGA TERHADAP KEPUTUSAN PEMBELIAN DENGAN KEPUASAN KONSUMEN SEBAGAI VARIABEL MEDIASI PADA AIR MINUM NESTLE PURE LIFE - Diva Vikani Anggraeni; Muhammad Mathori (LPPM Universitas Sains dan Teknologi Komputer, 2025)
This study aims to analyze the effect of price on purchasing decisions with consumer satisfaction as a mediating variable on Nestlé Pure Life drinking water products. The type of research used in this study uses a quantitative study by distributing questionnaires via google form which are distributed online. The sample in this study were consumers who had bought nestle pure life drinking water in the Yogyakarta area. The number of samples used in this study were 100 respondents. The analysis technique used in this study uses the SmartPls version 3 program with Convergent Validity, Factor Loading, Average Variane Extraked (AVE), Discriminant Validity, Fornel Larcker, Cross Loading, Reliability, Cronbach Alpha, Composite Reliability, R Square, and Hypothesis Testing tests. The results of this study indicate that price has a significant effect on customer satisfaction, price has a significant effect on purchasing decisions, customer satisfaction has a significant effect on purchasing decisions and the effect of price on purchasing decisions mediated by customer satisfaction.